Program Literasi di SDN 006 Terpadu Kubang Jaya, SDN 019 Koto Baru, SDN 037 Karya Indah, dan SDN 044 Karya Indah - Meisy Adhariani; Mutiara Nur Afifah; Nurlaila Saharani; Putri Gayo Mahbengi; Febrina Dafit (CV. Ulil Albab Corp, 2023)
This study aims to describe the implementation of literacy programs in four elementary schools, namely SDN 006 Terpadu Kubang Jaya, SDN 019 Koto Baru, SDN 037 Karya Indah, and SDN 044 Karya Indah. The research method used is a descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the four schools have implemented literacy programs well through integrating literacy into the curriculum, using creative learning methods, utilizing existing resources, and working with parents. This literacy program has had a positive impact in increasing students' interest in reading, reading, writing and speaking abilities. However, there are several challenges that need to be overcome, such as limited resources and inadequate support from related parties. This research provides recommendations for developing and improving literacy programs in elementary schools as an effort to form a generation that is literate and critical in reading and writing.